Validation of the HCM Risk-SCD model in patients with hypertrophic cardiomyopathy following alcohol septal ablation. Issue Volume 20:Issue FI 2(2018) (18th September 2017) - Liebregts, Max; Faber, Lothar; Jensen, Morten K; Vriesendorp, Pieter A; Hansen, Peter R; Seggewiss, Hubert; Horstkotte, Dieter; Adlova, Radka; Michels, Michelle; Bundgaard, Henning; ten Berg, Jurriën M; Veselka, Josef
Abstract: Aims: The HCM Risk-SCD model for prediction of sudden cardiac death (SCD) in hypertrophic cardiomyopathy recommended by the 2014 European Society of Cardiology (ESC) guidelines has not been validated after septal reduction therapy. The aim of this study was to validate the HCM Risk-SCD model in patients undergoing alcohol septal ablation (ASA) and to compare its performance to previous models. Methods and result: A total of 844 ASA patients without prior SCD event were included. The primary endpoint was a composite of SCD and appropriate implantable cardioverter defibrillator (ICD) therapy, identical to the HCM Risk-SCD endpoint. A distinction between periprocedural (≤30 days) and long-term (>30 days) SCD was made to discern procedure-related adverse arrhythmic events caused by the ASA-induced myocardial infarction from long-term SCD risk. Twenty patients reached the SCD endpoint within the first 30 days. During a follow-up of 6.5 ± 4.2 years, another 46 patients reached the SCD endpoint. The predicted 5-year SCD risk according to the HCM Risk-SCD model was 5.1%, and the observed 5-year SCD risk was 4.0%. The C-statistics for the use of the HCM Risk-SCD model was 0.61 ( P = 0.02), the C-statistics for the use of the 2003 American College of Cardiology/ESC guidelines was 0.59 ( P = 0.051), and the C-statistic for the use of the 2011 American College of Cardiology Foundation/American Heart Association guidelines was 0.58 ( P = 0.054). Maximal left ventricular wall thickness, syncope after ASA, and fulfilling the 2014 ESC recommendations for primary ICD implantation according to the HCM Risk-SCD model, respectively, predicted SCD during long-term follow-up. Conclusion: The HCM Risk-SCD model can be used for SCD prediction in patients undergoing ASA.